THE EFFECT OF BASIL LEAF EXTRACT (Ocimum sanctum) ON THE QUALITY OF FRESH NILE TILAPIA (Oreochromis niloticus) DURING ROOM TEMPERATURE STORAGE - Rahmi, Fauziah; Sari, N. Ira; Iriani, Dian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstract            This research aims to determine the effect of basil leaf extract (Ocimum sanctum) on the quality of fresh nile tilapia (Oreochromis niloticus) during storage at room temperature in terms of microbiological, organoleptic, and chemical parameters. The treatments are given consisted of K0 (control), K1 (10% basil leaf extract), K2 (15% basil leaf extract). The analysis parameters observed were the calculation of the total plate count, the organoleptic quality test, and the Total Volatile Base test. The result shown that K1 treatment (10% basil leaf extract) was the best treatment with the yellowish red flesh appearance criteria, rather bright, clean, neat, attractive and the lines formed from the spine and lateral linea are red, dim and not split, fresh odor criteria, fairly elastic texture criteria, rather soft, compact and good taste, specific taste of fresh fish, little leaf taste (bitter) and total plate count value of 5.9 x 103 colonies/gram and Total Volatile Base value of 22 mg/N for 9 hours of storage.Keywords: Ocimum sanctum, Oreochromis niloticus, Quality of fish.